2021
DOI: 10.3390/atmos12020268
|View full text |Cite
|
Sign up to set email alerts
|

Satellite-Based Personal UV Dose Estimation

Abstract: Epidemiology and public health research relating to solar ultraviolet (UV) exposure usually relies on dosimetry to measure UV doses received by individuals. However, measurement errors affect each dosimetry measurement by unknown amounts, complicating the analysis of such measurements and their relationship to the underlying population exposure and the associated health outcomes. This paper presents a new approach to estimate UV doses without the use of dosimeters. By combining new satellite-derived UV data to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…This work is also intended to serve this purpose. A classification is therefore difficult and can only be compared with modelling [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…This work is also intended to serve this purpose. A classification is therefore difficult and can only be compared with modelling [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…A further miniaturization of sensors to millimeter scale with wireless communication to standard consumer devices [ 359 ] will widen the scope of how these sensors can be deployed. Other studies have also shown that useful personal exposures to UV radiation can be achieved from satellite-based UV radiation estimates combined with exposure ratio modeling to account for individual factors [ 360 ] or by leveraging UV data from local research stations [ 361 ].…”
Section: Advances In Uv Monitoring and Modelingmentioning
confidence: 99%
“…Both intraday and interday accuracy and precision data showed good reproducibility. This method was successfully applied to pharmacokinetics studies 14 .…”
Section: Uv Estimationmentioning
confidence: 99%